The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1093/hmg/dds409
|View full text |Cite
|
Sign up to set email alerts
|

The ciliary Evc/Evc2 complex interacts with Smo and controls Hedgehog pathway activity in chondrocytes by regulating Sufu/Gli3 dissociation and Gli3 trafficking in primary cilia

Abstract: Hedgehog (Hh) signaling is involved in patterning and morphogenesis of most organs in the developing mammalian embryo. Despite many advances in understanding core components of the pathway, little is known about how the activity of the Hh pathway is adjusted in organ- and tissue-specific developmental processes. Mutations in EVC or EVC2 disrupt Hh signaling in tooth and bone development. Using mouse models, we show here that Evc and Evc2 are mutually required for localizing to primary cilia and also for mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
140
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(153 citation statements)
references
References 41 publications
12
140
1
Order By: Relevance
“…The same group also demonstrated compromised bone collar formation in Evc −/− mice in the C57BL/6 homogenous background but showed that both proliferation and differentiation of chondrocytes are compromised in mutant mice (Pacheco et al 2012). EVC and EVC2 are mutually required for their ciliary localization and loss of Evc2/Limbin results in similar skeletal phenotypes found in Evc −/− mice (Caparrós-Martín et al 2013;Zhang et al 2015).…”
Section: Primary Ciliamentioning
confidence: 81%
See 1 more Smart Citation
“…The same group also demonstrated compromised bone collar formation in Evc −/− mice in the C57BL/6 homogenous background but showed that both proliferation and differentiation of chondrocytes are compromised in mutant mice (Pacheco et al 2012). EVC and EVC2 are mutually required for their ciliary localization and loss of Evc2/Limbin results in similar skeletal phenotypes found in Evc −/− mice (Caparrós-Martín et al 2013;Zhang et al 2015).…”
Section: Primary Ciliamentioning
confidence: 81%
“…5) associated with dysregulated Ihh signaling in both the ISS and SOS at the neonatal stage, Patched1 expression is decreased in the perichondrium (Pacheco et al 2012), indicating that EVC and Kif3a/IFT88 regulate the synchondrosis with different mechanisms. Finally, EVC2 −/− mice also have impaired ISS development (Caparrós-Martín et al 2013). …”
Section: Primary Ciliamentioning
confidence: 99%
“…Simultaneously, Evc and Evc2 appear to be needed for the activation of pathway in the absence of Sufu (Caparrós-Martín et al, 2013). EVC syndrome shares some phenotypic similarities with OFDI, such as orofacial and nail abnormalities and T T T T T T T TT T T T T T T TT T T T T T T T T T T T T T T T TT T T T T T T T Novel homozygous mutations in the EVC Aziz et al 5 cardiovascular defects.…”
Section: Discussionmentioning
confidence: 99%
“…4), 21,22,142 and defective ciliary assembly is associated with defective cardiomyogenesis 21 as well as Hh-related heart defects that might be independent of nodal cilia, including ventricular and endocardial cushion-derived defects. 122,142,154 Further, 60% of patients with mutations in genes encoding the EVC proteins, EVC1/EVC2, which interact with Smo at the primary cilium to transduce Hh signaling [155][156][157][158][159] , display CHD, including AVSD and ASD. 47,51 In line with these findings, EVC proteins are coexpressed in the OFT and the mesenchymal structures of the atrial septa and AV cushions during heart development in mice 51 ; areas that are known to be ciliated during cardiogenesis.…”
Section: Cardiac Primary Cilia and Coordination Of Hedgehog Signalingmentioning
confidence: 99%